DARI ENKULTURASI KE DIGITALISASI: DINAMIKA PELESTARIAN KESENIAN DEBUS DI PADEPOKAN PUTRA KIARA TASIKMALAYA PADA ERA SMART SOCIETY 5.0 - Yusi Yustisian Adlah; Azka Khalif Faqih Aulia; Dini Nuranjani; Risa Miladiyati (Universitas Warmadewa, 2026)
Indonesia is a pluralistic nation with rich and diverse cultural heritage, including traditional performing arts imbued with local wisdom values. However, in the era of smart society 5.0, the preservation of traditional culture faces serious challenges due to the dominance of digital technology and foreign cultural influences. This study aims to examine the development, procedures, inheritance patterns, and preservation challenges of debus traditional art at Padepokan Putra Kiara, Karangjaya District, Tasikmalaya Regency, in the smart society 5.0 era. This research employs a descriptive qualitative approach with data sources comprising observation results, in-depth interviews with the padepokan's elders and players, literature review, and field documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results reveal that Padepokan Putra Kiara manages two variants of debus, namely Verification Debus and Invulnerability Debus, which previously required every prospective player to master three fundamental elements: breath control, sense refinement, and heart cultivation. The inheritance pattern proceeds informally through enculturation and socialization processes, from elders to community leaders, and subsequently to the next generation through experiential learning. Major challenges include public misconceptions regarding the mystical elements of debus, low interest among youth, and the economic limitations of practitioners. Recommended preservation strategies encompass performance digitalization, social media utilization, and collaboration with the creative industry to maintain debus's relevance in the modern era.